Effect of nutritional immunomodulation and heat stress during the dry period on subsequent performance of cows - Fabris, Thiago F.; Laporta, Jimena; Corra, Fabiana N. [UNESP]; Torres, Yazielis M.; Kirk, David J.; McLean, Derek J.; Chapman, J. D.; Dahl, Geoffrey E. (Elsevier B.V., 2017)
Heat stress in dairy cows during the dry period impairs milk yield in the next lactation. Feeding Omni-Gen-AF (OG; Phibro Animal Health Corp., Teaneck, NJ) to lactating cows during heat stress may increase dry matter intake (DMI) and lowers respiration rate (RR) and rectal temperature (RT), but the effects in dry cows are not known. We hypothesized that OG supplementation before, during, and after the dry period (approximately 160 d total) would overcome the effects of heat stress and improve cow performance in the next lactation. Cows were randomly assigned to OG or control (placebo) treatments for the last 60 d in milk (DIM), based on mature-equivalent milk yield in the previous lactation. Cows were dried off 45 d before expected calving and randomly assigned to heat stress (HT) or cooling (CL) treatments. Thus, cows received dietary supplementation during late lactation before they were exposed to either CL or HT. After dry-off, treatment groups included heat stress with placebo (HT, only shade, 56 g/d of placebo, n = 17), HT with OG supplementation (HTOG, 56 g/d of OG, n 19), cooling with placebo (CL, shade, fans, and soakers, 56 g/d of placebo, n = 16), and CL with 00 supplementation (CLOG, 56 g/d of OG, n = 11). After parturition, all cows were kept under the same CL system and management, and all cows continued to receive OG or control treatment until 60 DIM. Cooling cows during the dry period reduced afternoon RT (CL vs. HT; 38.9 +/- 0.05 vs. 39.3 +/- 0.05 degrees C) and RR (CL vs. HT; 45 +/- 1.6 vs. 77 +/- 1.6 breaths/min). Respiration rate was also decreased by OG supplementation under HT conditions (HTOG vs. HT; 69.7 +/- 1.6 vs. 77.2 +/- 1.6 breaths/min). An interaction was observed between OG supplementation and HT; HTOG cows tended to have lower morning RT compared with HT cows. During the dry period, OG reduced DMI relative to control cows. Birth weight was greater in calves from CL cows (CL vs. HT; 40.6 +/- 1.09 vs. 38.7 +/- 1.09 kg). No differences were detected among treatments in hematocrit, total protein, and body condition score. Cows offered CLOG, CL, and HTOG treatments had greater body weight during the dry period (794.9 +/- 17.9, 746.8 +/- 16.7, and 762.9 +/- 14.9 kg, respectively) than HT cows (720 +/- 16.2 kg). Gestation length was approximately 4 d longer for CL cows compared with HT cows. Cows offered CLOG, CL, and HTOG treatments produced more milk (41.3 +/- 1.6, 40.7 +/- 1.6, and 40.5 +/- 1.6 kg/d, respectively) than HT treatment (35.9 +/- 1.6 kg/d). Body weight after parturition and DMI were evaluated up to 60 DIM and averaged 661.5 +/- 15.8 and 19.4 +/- 0.7 kg/d, respectively, with no differences observed among treatments. These results confirm that exposure of dry cows to heat stress negatively affects milk yield in the subsequent lactation. Active cooling of dry cows and OG supplementation can reduce the negative effects of heat stress in the dry period on subsequent performance.
Keywords: dairy cow; cooling system; heat stress; dry period; OmniGen-AF